Hepatitis B and Hepatitis C Virus Infection in Haemodialysis Patients (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Hepatitis B virus (HBV) and Hepatitis C virus (HCV) infection are important causes of morbidity and mortality amongst haemodialysis (HD) patients.Objective: Study was conducted to investigate clinical, laboratory parameters of HCV and HBV infection at nephrology and dialysis centre, Combined Military Hospital, Dhaka, Bangladesh.Methods: It was an cross-sectional study. One hundred and twenty one end stage renal disease (ESRD) patients on maintenance HD, 88 male, 33 female, mean age 51.88 years (range 1485 years) were included in this study. Clinical and laboratory data such as age, sex aetiology of End Stage Renal Disease (ESRD), HBsAg and anti HCV, HBeAg, PCR for HCV RNA, serum bilirubin, ALT, AST, albumin were examined.Results: The ttest and Chi-Square Tests were used to analyse the significance of the results. Among HD patients HBsAg and anti HCV prevalence rate was 9.1% and 27.3% respectively. Diabetes mellitus and hypertension were common causes of ESRD.Conclusion: Prevalence of HBV and HCV infection is quite high in our HD patients, data emphasise need for strict adherence to infection control, barrier precaution and preventive behaviours.Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014